A new journey of fluorescent carbon dots: A shining star in the realm of nucleic acid dyes - Yu Ma; Bin Zhao; Guozhen Yan; Ting Zhou; Zhihua Xu; Zhihan Niu; Zhenghong Xu; Tongtong Zhang; Feng Shi (Materials & Design)
Nucleic acid dyes play important roles in the quantification and detection of nucleic acids by binding to nucleic acids. However, traditional nucleic acid dyes pose great environmental and economic challenges due to their high price, high toxicity, long dyeing time, low sensitivity and insufficient stability. To overcome these problems, we developed a new nucleic acid dye based on carbon dots, which were generated through hydrothermal synthesis with liquorice components as precursors and a system containing ethylenediamine. This new type of carbon dot can effectively replace traditional dyes and can be used to efficiently visualize DNA, RNA and plasmids via agarose gel electrophoresis. Then, we studied the interaction mechanism between carbon dots and nucleic acids by UV–visible spectroscopy, Fourier transform infrared spectroscopy and circular dichroism spectroscopy. The interaction between the carbon dots and nucleic acids mainly occurred through groove binding and was accompanied by a slight electrostatic interaction. Carbon dots-based nucleic acid dyes, with their low cost, simple synthesis process and high stability, have opened a new path for the field of nucleic acid detection. Its research and development not only promote the frontier progress of biological science and medicine but also introduces innovative strategies and tools for scientific research and clinical practice.